Rendimento dos não-componentes da carcaça de cordeiros de diferentes genótipos - Pinheiro, R. S B [UNESP]; Silva Sobrinho, A. G. [UNESP]; Gonzaga Neto, S.; Yamamoto, S. M. [UNESP]; Mourão, R. C. [UNESP]; Homem, A. C. [UNESP]; Santos, V. C. [UNESP] (My University, 2008)
Non-carcass components percentages of lambs terminated in confinement, fed with diet containing 40:60 forage:concentrate ratio were influenced by lambs' breed (Morada Nova and 1/2 Somális Brasileira 1/2 Morada Nova), except for the liver, without difference between pure and crossbred animals, with average values of 2.29% and 0.35%, respectively. Crossbred lambs had higher percentages of skin (8.96%), head plus foot (10.68%), heart (0.88%), and kidney (0.93%) than purebred lambs (7.15%, 9.69%, 0.56% and 0.35%, respectively).
Cuts and non-carcass components yield of lambs from different genotypes
Keywords: Crossbreeding; Liveweight components; Sheeps; Animalia; Ovis aries